Inviting understanding a portrait of invitational rhetoric - Foss, Sonja K., 1950-; Griffin, Cindy, 1957- (Rowman & Littlefield, 2020)
"Inviting Understanding provides a comprehensive, coherent portrait of invitational rhetoric in a way that allows readers to understand the theory, to explore possible extensions, to see the practices of invitational rhetoric at work, and to access a comprehensive bibliography of works on the subject"--